An outbreak of type B botulism in southern Viet Nam, 2020 - Ho, Tinh Huu; Nguyen, Ha Phan Ai; Le, Nhan Dinh Trong; Hoang, Phuong Hoai; Ha, Ninh Thi; Dang, Chinh Van (Western Pacific Surveillance and Response, 2022)
Objective: To investigate the cause of a botulism outbreak in several provinces in Viet Nam in 2020.Methods: An initial investigation was conducted to confirm the outbreak and to form hypotheses about the potential causes, followed by a case–control assessment of the plausible causative food item. Collected food samples were tested to identify the pathogen, and mouse bioassays were performed. Control measures were introduced to stop the outbreak and to prevent similar events in the future.Results: Twelve people in six southern provinces of Viet Nam were identified as having symptoms of botulism, of whom 11 were in critical condition requiring breathing support. A history of foods eaten in the 4 days before illness onset indicated that all the cases had eaten a tinned vegetarian pate, and a case–control assessment showed that this was significantly associated with the outbreak, with an odds ratio of 35.2 (95% confidence interval: 3.4–infinity). Clostridium botulinum type B was detected in three of eight pâté samples collected from the houses of cases. In the mouse bioassay for the toxicity of the pâté samples, all the mice died with clinical symptoms of botulism.Discussion: A tinned vegetarian pate was the plausible cause of a botulism outbreak in Viet Nam in 2020. Revision of food safety regulations to improve quality control of tinned foods to prevent future outbreaks is recommended.